2016
DOI: 10.1186/s12864-016-3361-3
|View full text |Cite
|
Sign up to set email alerts
|

Systematic analysis of the lysine acetylome in Fusarium graminearum

Abstract: BackgroundLysine acetylation in proteins is a ubiquitous and conserved post-translational modification, playing a critical regulatory role in almost every aspect of living cells. Although known for many years, its function remains elusive in Fusarium graminearum, one of the most important necrotrophic plant pathogens with huge economic impact.ResultsBy the combination of affinity enrichment and high-resolution LC-MS/MS analysis, large-scale lysine acetylome analysis was performed. In total, 577 lysine acetylat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

6
71
1

Year Published

2017
2017
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 44 publications
(78 citation statements)
references
References 52 publications
6
71
1
Order By: Relevance
“…Emerging evidence shows that lysine acetylation plays a major role in metabolism regulation and frequently occurs in almost all enzymes in the central carbon metabolism (Wang et al ., ), so we investigated the acetylation of metabolic enzymes in A. flavus by mapping acetylated proteins to Kyoto Encyclopedia of Genes and Genomes (KEGG) pathways (Table S5). Consistent with previous findings on lysine acetylation (Henriksen et al ., ; Li et al ., ; Zhou et al ., ), a large proportion of metabolic enzymes involved in central metabolism were acetylated, such as enzymes involved in the pentose phosphate pathway, glycolysis/gluconeogenesis and citric acid cycle (Fig. ), implying that lysine acetylation may regulate cellular metabolic processes at multiple levels.…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations
“…Emerging evidence shows that lysine acetylation plays a major role in metabolism regulation and frequently occurs in almost all enzymes in the central carbon metabolism (Wang et al ., ), so we investigated the acetylation of metabolic enzymes in A. flavus by mapping acetylated proteins to Kyoto Encyclopedia of Genes and Genomes (KEGG) pathways (Table S5). Consistent with previous findings on lysine acetylation (Henriksen et al ., ; Li et al ., ; Zhou et al ., ), a large proportion of metabolic enzymes involved in central metabolism were acetylated, such as enzymes involved in the pentose phosphate pathway, glycolysis/gluconeogenesis and citric acid cycle (Fig. ), implying that lysine acetylation may regulate cellular metabolic processes at multiple levels.…”
Section: Resultsmentioning
confidence: 99%
“…In addition, the proportion of identified acetylated proteins to the total protein (5.39%) in A. flavus is much lower than that in S. cerevisiae (17.93%) (Henriksen et al ., ), but close to filamentous fungi C. albicans (5.28%) (Zhou et al ., ) and B. cinerea (5.82%) (Lv et al ., ). The protein–protein interaction results also showed that the acetylated proteins are involved in many metabolic processes, which are consistent with the results of acetylomic analysis in the plant pathogenic fungi F. graminearum (Zhou et al ., ) and Phytophthora sojae (Li et al ., ).…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…of K ac sitesNo. of K ac proteins% of acetylationReferencesYeasts Y. lipolytica 64723163142822.1This study S. cerevisiae 54042878105919.6Henriksen et al (2012)Fungi P. sojae 19,027219711506.0Li et al (2016) B. cinerea 1638915829545.82Lv et al (2016) F. graminearum 13,3345773642.73Zhou et al (2016)Bacteria B. amyloliquefaciens 38113268125432.9Liu et al (2016) M. tuberculosis 4034112865816.3Xie et al (2015) Synechocystis sp.367277651314.0Mo et al (2015) V. parahemolyticus 4823141365613.6Pan et al (2014) S. reseosporus 689111436679.7Liao et al (2014) E. coli 414410703498.4…”
Section: Discussionmentioning
confidence: 96%